2021
DOI: 10.1080/87565641.2021.1988086
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Executive Functions, Theory of Mind, and Functional Outcomes in Middle Childhood

Abstract: This study examined whether hot and cool executive functions (EFs) differentially predicted functional outcomes and the independent and mediating roles of theory of mind (ToM). 126 children completed tests of hot and cool EF, ToM, intelligence, and academic achievement. Parents completed questionnaires of peer problems and prosocial behavior. Hot and cool EFs differentially predicted intelligence and academic achievement, supporting a hot-cool distinction. ToM predicted word reading and prosocial behavior but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
5
0
2
Order By: Relevance
“…It should be noted that the Strange Stories task was used only for assessing older children (approximately 6 -17 years old). Significant correlations were detected between the Strange Stories total score and WM, IC cool and ho t, and SH (ages 6-12 years) (Austin et al, 2014;Bock et al, 2015;Wilson et al, 2021). Performance in the Strange Stories task was also found to be predicted by IC and SH in adolescence (ages 13-18 years) (Gabriel et al, 2019) and also by WM (ages 6-18 years old) (Cantin et al, 2016;Gabriel et al, 2019).…”
Section: Tom Scales and Efsmentioning
confidence: 82%
“…It should be noted that the Strange Stories task was used only for assessing older children (approximately 6 -17 years old). Significant correlations were detected between the Strange Stories total score and WM, IC cool and ho t, and SH (ages 6-12 years) (Austin et al, 2014;Bock et al, 2015;Wilson et al, 2021). Performance in the Strange Stories task was also found to be predicted by IC and SH in adolescence (ages 13-18 years) (Gabriel et al, 2019) and also by WM (ages 6-18 years old) (Cantin et al, 2016;Gabriel et al, 2019).…”
Section: Tom Scales and Efsmentioning
confidence: 82%
“…In line with this, Lecce et al (2021) found associations between ToM and reading comprehension in older (9‐year‐old) children. However, other studies indicate that ToM is also related to basic reading skills, like word reading (e.g., Wilson et al, 2021) or letter knowledge (Blair & Razza, 2007). In our sample, at 5 years of age, only a minority of children understood second‐order FBs, whereas the majority performed well on first‐order FB tasks.…”
Section: Discussionmentioning
confidence: 98%
“…To measure familial SES, each parent's highest educational qualification was converted into scores ranging from 1 to 9 with no formal schooling (a), primary (b), secondary (c), post-secondary general and vocational (i.e., for technical professions), (d), polytechnic diploma (i.e., a 3 years course program that enable students to join the workforce or apply for university) (e), professional qualification and other diploma (f), bachelor's degree or equivalent (g), postgraduate diploma or certificate (h), master's and doctorate or equivalent (i). Given that the development of EF and language skills may influence children's social abilities (Wilson et al, 2021) we measured and analysed participants' performance in the forward digit span task from the Wechsler Intelligence Scale for Children-Fourth Edition (Wechsler, 2003), and in the Letter-Word Identification and Passage Comprehension tasks from the Woodcock-Johnson Tests of Achievement (McGrew et al, 2014;Schrank et al, 2014). A composite reading ability score was calculated from the W-scores of both tasks according to the test's guidelines (McGrew et al, 2014), such that higher scores indicated better reading ability.…”
Section: Methodsmentioning
confidence: 99%